Modeling and control of dynamic systems - Macia, Narciso F. (Thomson Delmar Learning, 2005)
Modeling and Control of Dynamic Systems teaches the basic concepts of control systems analysis and design. The book first focuses on understanding the basic building blocks of the dynamic systems surrounding us - electrical, fluid, mechanical, and thermal - and presents both traditional and modern tools for analyzing and predicting their behavior. Feedback control is presented so readers understand how to develop controllers to affect system behavior. MATLAB/Simulink is a powerful and easy-to-use software used in the text to troubleshoot, analyze and design dynamic systems.